Bending and Shear Experimental Tests and Numerical Analysis of Composite Slabs Made Up of Lightweight Concrete - F. P. Alvarez Rabanal; J. Guerrero-Muñoz; M. Alonso-Martinez; J. E. Martinez-Martinez (Journal of Engineering)
The aim of this paper is to understand the structural behaviour of composite slabs. These composite slabs are made of steel and different kinds of concrete. The methodology used in this paper combines experimental studies with advanced techniques of numerical simulations. In this paper, four types of concrete were used in order to study their different structural strengths in composite slabs. The materials used were three lightweight concretes, a normal concrete, and a cold conformed steel deck which has embossments to increase the adherence between concrete and steel. Furthermore, two lengths of slabs were studied to compare structural behaviours between short and long slabs. m-k experimental tests were carried out to obtain the flexural behaviour of the composite slabs. These tests provide dimensionless coefficients to compare different sizes of slabs. Nonlinear numerical simulations were performed by means of the finite element method (FEM). Four different multilinear isotropic hardening laws were used to simulate the four concretes. Coulomb friction contact was used to model the coefficient of friction between steel and concrete. Finally, a chemical bond was included to consider sliding resistance in the contact surface between steel and concrete. Experimental and numerical results are in good agreement; therefore, numerical models can be used to improve and optimize lightweight composite slabs.